Drug Utilization of Rifaximin-α in Patients with Hepatic Encephalopathy: Evidence from Real Clinical Practice in Italy - Valentina Perrone; Marcello Usala; Chiara Veronesi; Maria Cappuccilli; Luca Degli Esposti (Medicina)
Background and Objectives: This analysis described rifaximin utilization in Italian patients with hepatic encephalopathy (HE). Although rifaximin is effective in preventing HE relapses, therapeutic management and prescriptive attitudes might be improved. Materials and Methods: Between Oct-2020 and Sep-2021, approximately 12.7 million citizens, patients hospitalized for HE, were identified through the ICD-9-CM code 572.2. Among those discharged alive, utilization of rifaximin 550 mg vs. rifaximin 200 mg for two months post-admission was compared. Results: Of 634 patients hospitalized for HE, 447 (70.5%) were discharged alive. In the two following months, 276 (61.7%) received rifaximin, of whom 117 (26.2%) received rifaximin 550 mg (two daily tablets) and 159 (35.6%) received rifaximin 200 mg (six daily tablets); among 171 patients without rifaximin, 56 (32.7%) received lactulose/lactitol. One year after rifaximin initiation, patients on rifaximin 550 mg (vs. 200 mg) were more frequently persistent (i.e., did not interrupt therapy) (78.6% vs. 46.9%, p < 0.001), showed a lower switching proportion (21.4% vs. 40.7%, p < 0.050), and had a mean monthly dose closer to the recommendations of 36,000 mg/month (~33,000 mg/month vs. 11,629 mg/month, respectively). Conclusions: This analysis suggests suboptimal rifaximin utilization for HE management. Although rifaximin 550 mg is the only formulation with specific indication and reimbursability to prevent HE relapses in Italy, rifaximin 200 mg is more largely used. The need to improve rifaximin prescribing choices is supported by higher persistence, lower switching rates, and average doses aligned to recommendations in patients treated with rifaximin 550 mg.